'Now she wanna lick my plum': Azealia Banks and the undoing of antiblackness. Issue 2 (1st November 2018) - Burton, Justin Adams
In the first verse of Azealia Banks's 2011 '212', the singer tells us of a 'she' who wants to lick her 'plum'. Banks commits to the encounter, announcing, 'I guess that cunt gettin eaten', then chanting the line over and over. After a few iterations, though, a filter sweep slowly swallows her voice, leaving the listener to fill in the rest of the chant's vocals. Here, I consider this moment as a sonic 'undoing' of Banks's vocals that results in her voice crossing over into listeners' bodies. I contextualize this sonic undoing in terms of Karen Barad's theory of 'agential cuts', which separate otherwise entangled matter, then filter this through Sylvia Wynter's work on rebellion, which she defines as an undoing of the negation of 'Black peoples in slave and postslave eras'. Listening alongside Wynter and Katherine McKittrick, I argue that Banks's sonic undoing is also a rebellious performance of queer Black affirmation.